2012
DOI: 10.1134/s1995425512020047
|View full text |Cite
|
Sign up to set email alerts
|

Stable nitrogen isotopes (d15N) in thalli of arid vagrant lichen Xanthoparmelia camtschadalis across an altitudinal gradient of the Khangai Plateau of Mongolia

Abstract: The d 15 N values of stable nitrogen isotopes were determined in samples of organic matter (OM) of thalli of vagrant lichen Xanthoparmelia camtschadalis collected across 13 altitudinal levels within the range of 1550-3250 m above sea level of both steppes and highland meadows of the Khangai Plateau of Mongolia.No correlation between the d 15 N values of lichen OM and the altitude range was detected at the regional scale. However, at a local scale including vegetation type, botanical geographical area of Khanga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In line with Vidal-Russell & Messuti [46], who found that having cyanobacteria as the main photobiont has a strong phylogenetic signal, our results reflect the high conservatism of the photobiont partner within the three studied orders. Caliciales and Lecanorales had green algae versus Peltigerales with nitrogen-fixation by cyanobacteria apart from the general nitrogen inflow from deposition [47]. Conversely, variation in Chlb, NPQI, STM, WHC and δ 13 C was mainly observed at the species level, suggesting that the species-level quantification becomes necessary in these traits.…”
Section: (B) Most Functional Trait Variation Occurred Between Orders and Speciesmentioning
confidence: 95%
“…In line with Vidal-Russell & Messuti [46], who found that having cyanobacteria as the main photobiont has a strong phylogenetic signal, our results reflect the high conservatism of the photobiont partner within the three studied orders. Caliciales and Lecanorales had green algae versus Peltigerales with nitrogen-fixation by cyanobacteria apart from the general nitrogen inflow from deposition [47]. Conversely, variation in Chlb, NPQI, STM, WHC and δ 13 C was mainly observed at the species level, suggesting that the species-level quantification becomes necessary in these traits.…”
Section: (B) Most Functional Trait Variation Occurred Between Orders and Speciesmentioning
confidence: 95%
“…Plant studies have explored variation of plant isotopic ratios due to elevation (Kohzu et al, 2009;Biazrov, 2012;Casper et al, 2012), difference in water sources , and desertifi cation from vehicle travel (Li et al, 2006). Mammal studies have focused on the relationship between plant and mammal values within food webs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it should be possible to assess the extent to which mice rely on lichen at high elevations. Lichens are typically very 15 N-depleted relative to terrestrial plants (Fogel et al, 2008;Lee, Lim & Yoon, 2009;Pinho et al, 2017), and this holds true for lichens from high elevations (Biazrov, 2012;Marris et al, 2019;Szpak et al, 2013) and volcanic fumeroles (Tozer et al 2005). If lichen forms an important part of the diet of P. vaccarum at high elevations, we would expect to observe negative δ 15 N values.…”
Section: Introductionmentioning
confidence: 96%